A Systematic Review of Adaptation Measurement Instruments Based on Roy's Adaptation Model in the Nursing Context - Syamsidar, Syamsidar; Asmaningrum, Nurfika; Rondhianto, Rondhianto (STIKES Yayasan RS.Dr.Soetomo, 2025)
Background: Measurement of adaptation in nursing based on Roy's Adaptation Model is critical to understanding how patients adapt to chronic medical conditions. This model examines patient adaptation in four main modes: physiological, self-concept, role-function, and interdependence. This study aims to review and evaluate adaptation measurement instruments developed based on Roy's Adaptation Model, as well as assess their effectiveness and limitations in the context of nursing patients with chronic diseases. Methods: This study used a Systematic Literature Review (SLR) approach by following the PRISMA guidelines. The literature search was conducted systematically through reputable academic databases, such as Scopus, PubMed, Google Scholar, and DOAJ. The search strategy incorporated Boolean Operators to ensure broad coverage and topic relevance. The keywords used included measurement instruments, the Roy Adaptation Model, and aspects of validity and reliability. Studies included in this review contained information related to the development or application of patient adaptation measurement instruments with the Roy Adaptation Model in a nursing context. Selected articles were published between 2015 and 2025 and met strict inclusion and exclusion criteria. Results: Twenty articles were found that met the inclusion criteria. Adaptation measurement instruments based on Roy's Adaptation Model showed good validity and reliability, but had limitations in measuring all modes of adaptation holistically. Existing instruments are mostly applied in specific care contexts, such as patients with heart failure, neurodegenerative diseases, and palliative care. Some instruments only measure one or two modes of adaptation, which limits a comprehensive picture of the patient's adaptation process. Conclusions: Although the existing instruments are valid and reliable, there is still a need to develop more holistic instruments that can integrate all four modes of adaptation in one cross-culturally validated measurement tool. Future research is recommended to expand the application of the Roy Adaptation Model in various care contexts.